Teacher support of collective argumentation in mathematics classrooms: insights from an afterschool program - Francisco, John M. (Journal of mathematics teacher education, 2025)
Studies show that supporting argumentation in mathematics classrooms is challenging for teachers. This study reports on the experience of seven elementary and middle-school mathematics teachers in an afterschool classroom-based program where they had the opportunity to facilitate research sessions on students’ development of mathematical ideas and different types of reasoning and justification. The study examines the teachers’ support of argumentation as students work collaboratively on challenging mathematical tasks. The results describe pedagogical strategies teachers can use to support students’ development of valid mathematical arguments and types of mathematical knowledge for teaching (MKT) that influence teachers’ supporting efforts.